The Story as a Didactic Resource for Teachers to Promote Reading Habits in 3-4-Year-Old Children." - Cusme Carrion, Nelly Stefania; Aguirre Calan, Gabriela Monserrate (Tierra Infinita, 2023)
The story is installed as a favorable resource for the approach of the infant to imaginative and creative reading. Therefore, its educational value is recognized in a significant way. Being a didactic resource in the school by the teacher, since it prepares for life, develops the habit of reading and contributes to the development of learning. The purpose of this study is to know if teachers use the story as a teaching resource, types of stories they use and if they develop reading through this educational resource. The methodology used is a descriptive-qualitative study, which applied a Likert scale survey with 12 closed questions to teachers of Initial Education I, in public and private institutions. The results show significant differences in importance, use, types, and interest of the story as a teaching resource. It is concluded that the story plays an important role in the child's learning in the development of social, cognitive and affective skills. Creating and fostering a reading habit in the infant.
Keywords: story; reading habit; educational resource